MANIFACTURING OF FOOD WITH GOOD NUTRITIONAL VALUE FOR TILAPIA NILOUTICA - LAOUAR Heyem (My University, 2024)
This study showed the effect of natural food produced during this study period on the weight development and growth rate of 100 fry individuals from a population of Nile tilapia (Oreochromis niloticus) from the El Marssa Skikda farm, during the period from 06/05/2024 to 04/06/2024. During this study period, we measured the physicochemical parameters in the three tanks with different food compositions (tank 1: control (industrial food); tank 2: (manufactured natural food); tank 3: (Spirulina and manufactured food).Furthermore, growth was estimated in the three tanks using the V. Bertallanfy 1985 model, using the Statistica 8 software. Indeed, we note variations in the physicochemical parameters from one tank to another and from one period to another. From the estimation of the growth of the individuals in this population, we concluded the type of allometry in the three tanks by comparison with b<3. Moreover, the comparison of the growth rate and weight of individuals in the three tanks reveals that the fry in tank 2 have a higher growth rate and body weight than those in the other two tanks (K= 0.864; Wt=2.6), confirming the high nutritional quality of the manufactured food. -------------------------------------------------------------------------------------------------------------------------------------- أظهرت هذه الدراسة تأثير التغذية الطبيعية المصنوعة خلال فترة الدراسة هذه، على تطور الوزن ومعدل النمو لعدد 100 فرد من زريعة البلطي النيلي(Oreochromis niloticus)، من مزرعة المرسى سكيكدة، خلال الفترة من 06/05/2024 إلى 04/06/2024. خلال فترة الدراسة هذه، قمنا بقياس المعايير الفيزيائية والكيميائية في ثلاثة أحواض ذات تركيبات غذائية مختلفة (الحوض 1: شاهد (تغذية صناعية)؛ الحوض 2: (تغذية طبيعية مصنوعة)؛ الحوض 3: (سبيرولينا وتغذية مصنوعة.(( من جهة أخرى، تم تقدير النمو في الأحواض الثلاثة بواسطة نموذج V. Bertallanfy 1985، باستخدام برنامج Statistica 8، حيث نلاحظ بالفعل وجود اختلافات في المعايير الفيزيائية والكيميائية من فترة لأخرى، ويتضح من تقدير نمو الأفراد لهذه المجموعة أننا استنتجنا نوع التوزيع في الأحواض الثلاثة من خلال المقارنة مع b<3. وعلاوة على ذلك، فإن مقارنة معدل النمو ووزن الأفراد في الأحواض الثلاثة تكشف أن زريعة الحوض 2 تظهر معدل نمو ووزن جسم أكبر من الأفراد في الحوضين الآخرين K= 0.864)؛ (Wt=2.6، مما يؤكد على الجودة الغذائية الجيدة للغذاء المصنوع. -------------------------------------------------------------------------------------------------------------------------------------- Cette étude a montré l’effet d’une alimentation naturel fabriqué au cours de cette période d’étude, sur l’évolution du poids et du taux de croissance de 100 individus d’alevins, d’une population de Tilapia (Oreochromis niloticus), provenant de la ferme d’El Marssa Skikda, durant la période 06/05/2024 a 04/06/2024. Dans cette période d’étude en a mesurés les paramètres physico chimiques dans les trois bacs de compositions alimentaires différentes (bac1 : témoin (alimentation industrielle) ; bac2 : (aliment fabriqué naturel) ; bac 3 : (Spiruline et aliment fabriqué). Par ailleurs, la croissance est estimée dans les trois bacs par le modèle de V. Bertallanfy 1985, en utilisant le logiciel Statistica 8. Nous notons en effet, des variations des paramètres physico chimiques d’un bac à l’autre et d’une période à l’autre, Il ressort de l’estimation de la croissance des individus de cette population, nous avons conclu type d’allométrie dans les trois bacs par la comparaison avec b<3. En outre, la comparaison du taux de croissance et du poids des individus dans les trois bacs, révèle que les alevins du bac 2 présentent un taux de croissance et un poids corporel plus important que ceux des deux autres bacs (K= 0.864 ; Wt=2.6), ce qui confirme la bonne qualité nutritive de l’aliment fabriqué.